Tribocorrosion behaviour of anodic titanium oxide films produced by plasma electrolytic oxidation for dental implants. (2nd July 2013) - Alves, S. A.; Bayón, R.; Igartua, A.; Saénz de Viteri, V.; Rocha, L. A.
ABSTRACT Commercially pure Titanium (cp‐Ti) and its alloys are the materials most widely used for dental implant applications. In the present work, anodic oxide films have been produced on cp‐Ti surfaces by plasma electrolytic oxidation (PEO) technique. After PEO treatments, oxide films with different surface features (e.g. surface roughness, morphology and film thickness) were obtained according with anodising parameters. The tribocorrosion behaviour of untreated and PEO‐treated Ti samples was investigated by reciprocating sliding tests performed in artificial saliva. PEO treatments significantly improved the performance of cp‐Ti substrates when they were submitted simultaneously to electrochemical and mechanical effects, and it was influenced by PEO processing parameters. PEO seems to be a very attractive technique for the development of bio‐tribocorrosion resistant Ti surfaces with potential for biomedical applications namely, for dental implants. Copyright © 2013 John Wiley & Sons, Ltd.